Orthopaedic Sports Medicine Podcasts Should Tailor Characteristics Such as Episode Length and Social Media Utilization for Best Audience Engagement - Justin A. Sedgewick, B.A; Evan P. Arnold, B.S; Michaela A. Stamm, M.S; Mary K. Mulcahey, M.D (Elsevier, 2022)
Purpose: To describe the growth and characteristics of active orthopaedic sports medicine podcasts. Methods: Three common podcasting platforms (Apple, Google, and Spotify) were queried July 24, 2021 using the search term "sports medicine." For each unique active podcast hosted by an orthopaedic surgeon, data were collected on year of the first episode, number of episodes, frequency of episodes, types of guests, topics discussed, episode length, and social media presence. Descriptive characteristics were then calculated. Results: 15 podcasts met inclusion criteria. Seven (46.7%) of these podcasts were started within 12 months of July 24, 2021. The most common episode release schedule was weekly, and podcast lengths averaged 21 minutes, 47 seconds (SD 17:17, range: 11:02-1:49:13). All podcasts featured guests, most often from a variety of sports medicine backgrounds. Social media platforms were commonly used by podcast hosts, with social media account follower numbers as high as over 100,000, and consistent engagement across three major social media platforms for most podcasts. Conclusions: This study found that episodes are typically released weekly and average 21 minutes, 47 seconds long, with most covering a wide array of topics in sports medicine. The Facebook accounts of these podcasts displayed higher numbers of followers compared to other social media platforms; however, Instagram was superior for engagement. Clinical Relevance: Orthopaedic sports medicine podcasts have an increasing presence and can be used to increase trainee engagement and public exposure via tailoring of podcast episode lengths and selection of social media platforms with high audience interaction.